Development of Antifungal Packaging for Berries Extruded from Recycled Pet - Junqueira-Conceicao Goncalve, M (2013)
In this study an active packaging was developed for marketing fresh berries by extruding recycled PET with potassium sorbate (KS) added as the antifungal agent at two concentrations (2.5 and 4.0wt.%). The mechanical, thermal and optical properties of the extrudate were characterized using Resistance to dynamic compression, Differential Scanning Calorimeter (DSC), and CIELAb colourimetry, respectively. The structure of the material was visualized using Scanning Electron Microscope (SEM) and its composition was examined using Fourier transform infrared spectroscopy (FTIR). The addition of KS introduced yellow colouration to the extrudate which increased with the concentration added. KS addition also lowered the packaging resistance against compression, but not to such an extent which precluded its application. The antifungal efficacy against Botrytis cinerea was determined by agar diffusion method, and the extent of fungal growth inhibition was found to increase with the concentration of KS. The specific migration of KS was also determined and was found to be well within regulatory compliance limits. © 2013 Elsevier Ltd.